DETERMINAN HARGA SAHAM MELALUI RISIKO KREDIT PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BEI - Bonna Marietta Bardo (2022)
This study is a quantitative study to determine the effect of the BI rate, economic growth, bank liquidity and capital adequacy on stock prices through credit risk as an intervening variable. The population of this study is the conventional commercial banks listed on the Indonesia Stock Exchange, amounting to 43 banks. Sample selection using nonprobability sampling. The data used is secondary data with panel data regression analysis method using E-views 10. The sample used is 36 Conventional Commercial Banks for the 2014-2020 period. This research uses signal theory to strengthen the research. The results of the study show that (1) the BI Rate has a significant negative effect on stock prices, (2) economic growth has no significant effect on stock prices, (3) bank liquidity has no significant effect on stock prices, (4) Capital adequacy has no significant effect on stock prices, (5) BI Rate has a significant negative effect on stock prices through credit risk, (6) economic growth has a significant positive effect on stock prices through credit risk, (7) bank liquidity has no significant effect on stock prices through credit risk, (8) Capital Adequacy has no significant effect on Stock Price through Credit Risk.